2014
DOI: 10.1155/2014/373286
|View full text |Cite
|
Sign up to set email alerts
|

Total Reconstruction of the Auricle: Our Experiences on Indications and Recent Techniques

Abstract: Introduction. Auricular reconstruction is a great challenge in facial plastic surgery. With the advances in surgical techniques and biotechnology, different options are available for consideration. The aim of this paper is to review the knowledge about the various techniques for total auricular reconstruction based on the literature and our experience. Methods. Approximately 179 articles published from 1980 to 2013 were identified, and 59 articles were included. We have focused on the current status of total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 49 publications
1
62
0
1
Order By: Relevance
“…12 Base on Weerda classification, morphological defect of right auricle at superior helix in this case belong in grade I malformations, sub group small deformities. 4 Characteristic of grade I malformations and small deformities in this case indicated that most structures of normal auricle are present, and small deformities of right auricle at superior helix were indentation ( Figure 1B, Figure 1D). Refer to the appearance of auricle abnormality turns out to involve a variety of auricular component malformations 3 and the term of means "small ear" although in the literature it applies to small or malformed ears, then small deformities of right auricle at superior helix in this case were indentation be able to classified in microtia.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…12 Base on Weerda classification, morphological defect of right auricle at superior helix in this case belong in grade I malformations, sub group small deformities. 4 Characteristic of grade I malformations and small deformities in this case indicated that most structures of normal auricle are present, and small deformities of right auricle at superior helix were indentation ( Figure 1B, Figure 1D). Refer to the appearance of auricle abnormality turns out to involve a variety of auricular component malformations 3 and the term of means "small ear" although in the literature it applies to small or malformed ears, then small deformities of right auricle at superior helix in this case were indentation be able to classified in microtia.…”
Section: Discussionmentioning
confidence: 70%
“…The size of normal auricle depends on various factors such as age, 4 gender, and body height has been reported. 2,4 The TEL in adults is about 58-66mm (in women 58-63 mm and men 62-66mm) and EB approximately 32-34mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations